3D fluorescence confocal microscopy of InGaN/GaN multiple quantum well nanorods from a light absorption perspective. Issue 9 (6th April 2021) - Gu, Yan; Liu, Yu shen; Yang, Guofeng; Xie, Feng; Zhu, Chun; Yu, Yingzhou; Zhang, Xiumei; Lu, Naiyan; Wang, Yueke; Chen, Guoqing
Abstract : SEM, confocal XZ and YZ cross-sectional images of nanorod arrays of InGaN/GaN MQW NRs. A ( λ ), T ( λ ) and R ( λ ) of InGaN/GaN MQW NR arrays. Abstract : A nanostructure of In0.18 Ga0.82 N/GaN multiple quantum well (MQW) nanorods (NRs) was fabricated using top-down etching with self-organized nickel (Ni) nanoparticles as masks on the wafer. The optical properties of In0.18 Ga0.82 N/GaN MQW NRs were discussed by experiment and theory from a light absorption perspective. Three-dimensional (3D) optical images of NRs were successfully obtained by confocal laser scanning microscopy (CLSM) for physical observation of the optical phenomenon of InGaN/GaN MQW NRs. Moreover, optical simulations were performed by COMSOL Multiphysics via the three-dimensional finite-element method to explore the influences of NR geometrical parameters on optical absorption. The simulated results demonstrate that the absorption of NRs is higher than that of the film due to the waveguide properties of NRs resulting from their higher refractive index than embedding medium and higher aspect ratio than bulk. In addition, an increase in the diameter results in a red-shift of the absorption peak position of In0.18 Ga0.82 N/GaN MQW NRs. The smaller pitch enhances the near-field coupling of the nanorods and broadens the absorption peak. These results clearly illustrate the optical properties of In0.18 Ga0.82 N/GaN MQW NRs from the perspective of 3D confocal laser scanning microscopy. This work is promising for the applications of III–V optoelectronic devices.